MULTICULTURAL EDUCATION AND SOCIETY EMPOWEREMENT BASED ON PESANTREN- MAJELIS TA'LIM - Heru Saputra; Heru Prastyo (MIYAH : Jurnal Studi Islam, 2021)
Abstract: This study aimed at describing the management of An-Najach Majelis Ta'lim, identifying lecture material from multicultural aspects, and the impact of Majelis Ta'lim in society. The research method used was descriptive qualitative through interviews, observation, and documentation. The place of the study was the Mejelis Ta’lim An-Najach housed in the Pesantren (Islamic boarding school) An-Najach Tegalrejo Magelang Indonesia. The results showed that: 1) every pengajian (Islamic teaching) session is attended by thousands of jamaahs from various societies, backgrounds, and cities. All jamaahs receive the same treatment: young-old, man-woman, rich-poor, and public officials are welcomed without discrimination. 2) There are many lectures with anti-multicultural material but do not cause conflict. 3) Mejelis Ta'lim An-Najach becomes the motor of the community's economic, social and spiritual empowerment. This study concluded that: first, the socio-economic empowerment of the community is determined by the quantity of the jamaahs. The greater the number of pilgrims, the greater the socio-economic prosperity of the community. Second, the da'wah bilhal (generosity) can reduce the hidden conflict even the da'wah contains the anti-multicultural view, as the jamaahs focus on spiritual values. Third, the empowerment of the surrounding community adds their respect to the pesantren and its leader regardless of the anti-multiculturalism teachingKeyword: Majelis Taklim, An-Najach, Abdul Mukti.